2012
DOI: 10.5296/ijhrs.v2i1.1310
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Factors Affecting Staffs Knowledge Sharing In the Central Library of the University of Isfahan Using the Extension of Theory of Reasoned Action

Abstract: The vital importance of knowledge management, in today’s complicated and changing environment as a source for strategic reconstruction of an organization cannot be denied. Furthermore, the effective sharing of knowledge is one of the most important success factors in an organization. This study aims at predicting the staff’s sharing of knowledge in the central library of the University of Isfahan. The conceptual framework for this study is consisted of the completed model of Theory of Reasoned Action. The stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
1
16
1
1
Order By: Relevance
“…Also, Alam et al (2009) in Awodoyin et al (2016) assert that self-efficacy affects an individual’s readiness to share knowledge. Moreover, Allameh et al (2012) in their study found that staff’s belief in their abilities acts as a strong motivation to share knowledge with colleagues.…”
Section: Discussion Of Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, Alam et al (2009) in Awodoyin et al (2016) assert that self-efficacy affects an individual’s readiness to share knowledge. Moreover, Allameh et al (2012) in their study found that staff’s belief in their abilities acts as a strong motivation to share knowledge with colleagues.…”
Section: Discussion Of Findingsmentioning
confidence: 95%
“…Also, the study revealed that extrinsic reward system had a significant relationship with SDGs actualization ( r = .883**; N = 72; p <0.01). Allameh et al (2012) found that the expected organizational rewards influence the staff’s attitude and intention for knowledge sharing significantly. Also, Al-Alawi et al (2007) showed a positive relationship between the existence of a reward system aligned with sharing and knowledge sharing in organizations.…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…Knowledge has been classified into tacit and explicit forms. According to Allameh et al (2012), tacit knowledge is in one’s thoughts and cannot be expressed, codified and recorded. Waterfield (2010) describes tacit knowledge as a tool that is used to handle or improve what is in focus.…”
Section: Background To the Studymentioning
confidence: 99%
“…Waterfield (2010) describes tacit knowledge as a tool that is used to handle or improve what is in focus. In contrast, explicit knowledge can be expressed, codified and formulated physically and electronically (Allameh et al, 2012).…”
Section: Background To the Studymentioning
confidence: 99%
“…According to Allameh et al, [7], sharing and distributing knowledge is positively linked to knowledge management, and knowledge sharing is based on individual behavior, as people do not accept the value of sharing knowledge unless they think it is important. Thus, changing people's behavior is the challenge in KM [8] and knowledge sharing behavior is the central process of KM.…”
Section: A Knowledge Sharingmentioning
confidence: 99%